Tooth Contact Analysis and Adjustment Calculation of Real Tooth Surfaces of Hypoid Gears - Han Kunpeng; Yang Jianjun (Jixie chuandong)
For the purpose of adjusting the calculation of the contact pattern of real hypoid gears, the double third-power spline surface is used for fitting tooth surfaces of pinions and gears accurately according to the measurement results of the gear surface. Based on the two-dimension golden section method for increasing the density of gear grid mesh points, the contact analysis algorithm for discrete real gear surface is established to carry out the contact information of real gear surface and adjust parameters of contact patterns, which is applied for adjusting of machining-tool settings conveniently. In the end, a hypoid gear pair of automobile driving axles is used to verify the feasibility and correctness of the proposed algorithm by rolling tests, which shows that the contact pattern by discrete tooth contact analysis is consistent with the real rolling test.